PENGARUH LITERASI EKONOMI DAN LINGKUNGAN SOSIAL TERHADAP PERILAKU PEMBELIAN IMPULSIF MELALUI ONLINE SHOP PADA PESERTA DIDIK KELAS X JURUSAN IPS DI SMA NEGERI 8 MAKASSAR - NONENG; TUTI SUPATMININGSIH; INANNA; MUHAMMAD HASAN; MUHAMMAD DINAR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study aims to determine the effect of economic literacy skills and the social environment on impulsive buying behavior through online stores. The research method used is research based on a quantitative approach. Methods of data through documentation and questionnaires. The results showed that: the literacy ability of students had no effect on impulsive buying behavior through online stores. In the study, it was also found that there was a positive and significant influence on the social environment on purchasing behavior made through online stores in class X students majoring in social studies at SMA Negeri 8 Makassar. There is a positive and significant effect of collaboration between economic literacy and the social environment on impulsive buying behavior through online stores for class X students majoring in social studies at SMA Negeri 8 Makassar